Research and Practice of Key Technologies of Inland Intelligent Ships - Xue-min, Song; Xu-ming, Wang; Wei-qin, Liu; Feng, Ma; Zhen, Huang; Xiao-qiang, Xu (2021 6th International Conference on Transportation Information and Safety (ICTIS), 2021)
This paper proposed an inland intelligent ship design whose key techniques (sensing technology, smart controller and virtual training technology) have been broken through recently by our team. In summary, the platform of these inland intelligent ships are designed based on the principles of aesthetic appearance, systems efficiency and growth potential. First of all, a smart controller of inland intelligent ship is developed in accordance with a self-adaptive PID-based algorithm. Meanwhile, the intelligence of perceiving environment is realized in account of information fusion methods. Furthermore, Virtual reality controlling, simulation and a training system were also provided. At present, the designed inland intelligent ship is capable of avoiding avoidance, planning routes, keeping course, tracking given tracks, and crossing narrow channels automatically. In summary, this research combines numerical calculation and model test to study a number of key techniques such as navigation intelligence, controlling intelligence and simulation train, lays a firm foundation for large-scale applications of inland intelligent ships.